2019
DOI: 10.1016/j.parepi.2018.e00078
|View full text |Cite|
|
Sign up to set email alerts
|

Spatiotemporal distribution and economic loss associated with bovine cysticercosis and human taeniasis in Ethiopia

Abstract: A metacestode stage (bovine cysticercosis) and adult stage Taenia saginata, accounted for zoonotic and economic losses from organ contamination and treatment cost. The objective of this paper is to assess the spatiotemporal distribution and economic loss from bovine cysticercosis and human taeniasis with treatment approach in different parts of Ethiopia. All available published research articles from Ethiopia on the disease were collected. The data were assessed using the current regional administrative, the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…Taeniosis due to T. saginata infection is an important public health concern globally, and has been reported in more than 77-million people worldwide, particularly in areas of Central and East African Africa, Asia, and highly endemic areas in the Mediterranean Region and the New World ( Hiko and Seifu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Taeniosis due to T. saginata infection is an important public health concern globally, and has been reported in more than 77-million people worldwide, particularly in areas of Central and East African Africa, Asia, and highly endemic areas in the Mediterranean Region and the New World ( Hiko and Seifu, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the prevalence of cysticercosis was reported to be 7%the at the national level by meta-analysis of previous studies ( Assefa and Bihon, 2019 ). Furthermore, spatiotemporal analysis based on previous studies conducted by ( Hiko and Seifu, 2019 ) indicated that the prevalence of C. bovis had high variability that ranged from 8 to 90% geographically. Furthermore, a more recent systematic review ( Jorga et al, 2020 ) also showed huge regional variation ranging from 2 to 25%.…”
Section: Introductionmentioning
confidence: 91%
“…A cisticercose é considerada, em vários países, uma das principais doenças parasitárias responsáveis por condenações e por riscos à saúde pública (2) . Os dados estimados para calcular o impacto econômico causado pela cisticercose bovina são coletados de várias fontes nos setores de carnes e incluem perdas de valor para carcaças infectadas, que passam por aproveitamento condicional, e custos com a condenação de carcaças (3) .…”
Section: Introductionunclassified